Community energy storage business case – Final report - Philip Leicester; Paul Rowley (2017)
Executive Summary This study explores the potential for energy storage to contribute to the delivery of resilient, low carbon and cost effective community-scale energy systems in order to provide insights for a range of stakeholders, including project developers, investors, policy makers and community organisations. The work involves an integra ted analysis of a number of candidate community-scale energy business models comprising both electrical and thermal energy storage, and ~he roles of key stakeholders involved in financing, delivering and operating such projects. It also includes the results of techno-economic modelling carried out for a range of technical platforms comprising embedded energy generation technologies utilised together with electrical and thermal energy storage systems. The insights provided are intended to underpin decision making in policy development, investment planning and project delivery as part of the UK's journey towards a cost-effective low-carbon energy infrastructure. The aims of the work covered in this study were: • To identify stakeholders in the community energy storage sector, and consider stakeholder roles, benefi ts and barriers • To evaluate potential business models, usin,g relevant recent studies as well as stakeholder input • To assess storage and re lated technologies in the near, medium and long terms, and identify candidate energy storage platforms at both device and system levels through a system-of-systems approach • To examine relevant markets for energy storage, and assess potential value streams applicable to community-scale projects • To carry out a financial feasibility and risk analysis study for specific community-scale scenarios The key findings of the work are summarised below.